2014
DOI: 10.1590/s0100-736x2014001000005
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Mycoplasma synoviae on commercial poultry farms of Pernambuco, Brazil

Abstract: Pesq. Vet. Bras. 34(10):953-956, outubro 2014 953 RESUMO.-[Ocorrência de Mycoplasma synoviae em granjas comerciais da avicultura de Pernambuco.] O estado de Pernambuco é o maior produtor de ovos da região Norte e Nordeste e ocupa a segunda posição na produção de frangos de corte. Os micoplasmas são importantes patógenos aviários que causam doenças respiratórias e sinovite que resultam em grandes perdas econômicas.Objetivou-se pesquisar a ocorrência de Mycoplasma gallisepticum (MG) e Mycoplasma synoviae (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The results obtained for the detection of MG are also similar to those of a study conducted at Pernambuco, in which 11 broilers and laying hens showed positive PCR and nested PCR for the presence of MG in seven samples (33.33%) (Barros et al, 2014); however, some flocks had clinical respiratory signs, unlike the flocks in the present study as evident in the ante-mortem inspection. In the state of Goiás, Minharro, Linhares, Andrade, Rocha and Santana (2001) also detected MG in 32.25% and MS in 25.80% swab samples from air sac injuries using PCR in broilers at slaughterhouses located at the municipalities of Itaberaí and Pires do Rio.…”
Section: Detection Of Mg and Ms Using Pcrsupporting
confidence: 88%
“…The results obtained for the detection of MG are also similar to those of a study conducted at Pernambuco, in which 11 broilers and laying hens showed positive PCR and nested PCR for the presence of MG in seven samples (33.33%) (Barros et al, 2014); however, some flocks had clinical respiratory signs, unlike the flocks in the present study as evident in the ante-mortem inspection. In the state of Goiás, Minharro, Linhares, Andrade, Rocha and Santana (2001) also detected MG in 32.25% and MS in 25.80% swab samples from air sac injuries using PCR in broilers at slaughterhouses located at the municipalities of Itaberaí and Pires do Rio.…”
Section: Detection Of Mg and Ms Using Pcrsupporting
confidence: 88%
“…Due to regular vaccination of the flocks, wild type MG prevalence is relatively low, not found using Positions where nucleotide differences exist in one sequence are denoted with the ambiguity setter code, according to the IUB. PCR by Buim et al (2009), Mettifogo et al (2013) and Barros et al (2014), 5% (Teixeira et al, 2015) and isolated from 2,67% of the flocks by Santos (2015). On the other hand, since flocks are not vaccinated for MS in Brazil, prevalence is estimated to be very high, with 79,31% (Buim et al, 2009), 68% (Mettifogo et al, 2013), 83,33% (Barros et al, 2014), 45% (Teixeira et al, 2015) and 93,34% (Santos, 2015).…”
Section: Resultsmentioning
confidence: 98%
“…PCR by Buim et al (2009), Mettifogo et al (2013) and Barros et al (2014), 5% (Teixeira et al, 2015) and isolated from 2,67% of the flocks by Santos (2015). On the other hand, since flocks are not vaccinated for MS in Brazil, prevalence is estimated to be very high, with 79,31% (Buim et al, 2009), 68% (Mettifogo et al, 2013), 83,33% (Barros et al, 2014), 45% (Teixeira et al, 2015) and 93,34% (Santos, 2015). However, isolation of pathogenic mycoplasmas may be difficulted by rapid growth of commensal strains, such as M. gallinarum and M. gallinaceum (Kleven, 2008).…”
Section: Resultsmentioning
confidence: 98%